Gender Wage Gap & Equality for All: The Case of a Financial Institution in Iceland - Karyn Kristín Drummond 1989- (2015)
In a world with a growing labour market and greater diversity than ever, gender equality in the workplace is becoming increasingly important. Despite great advances, the gender wage gap persists all over the world. Women are still being paid less than men for doing the same jobs and are facing discrimination in the workplace based on their sex. One of the financial institutions in Iceland is no exception, there have been problems relating to these issues within the organization. The purpose of this study is to examine the case of this financial institution in particular and see how they have attempted to tackle the gender wage gap. Common theories about the gender wage gap will be explained, namely the glass ceiling theory, sticky floor theory, and the human capital model. Other important topics relating to this issue will also be discussed, such as the trends in the gender wage gap, female gender constraints, pay expectations and maternity leave. The Icelandic labour market will be examined in particular, and comparisons will be made with other countries in the European Union and the initiatives they have taken on, as well as solutions the financial institution has been undertaking in order to fix their gender wage gap and gender equality issues. Some examples of what the financial institution has done are to create a gender equality committee and specific focus groups, signing the UN Equality Treaty, and obtaining an Equal Wage Certificate in order to commit to the Equal Wage Standard in Iceland. The methods taken to create this study will also be looked at in further detail. The specific initiatives will be described in depth and their practical applications for other organizations will be discussed so that the gender wage gap and gender inequality can potentially be put to an end worldwide.